ANALISIS POTENSI DAN INDEKS KERENTANAN PEMANFAATAN AIR TANAH DI KABUPATEN TANAH DATAR - Dilla, Fadilla; Umar, Iswandi (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This study aims to determine 1) the potential of groundwater in Tanah Datar District and 2) the vulnerability index of groundwater utilization in Tanah Datar District. This type of research is quantitative, which requires mathematical and statistical calculations in processing the data. Groundwater potential classes are obtained from the overlay results and scoring of several parameters such as land cover, NDVI, drainage density, geology, soil, slope, and rainfall. The groundwater potential map in Tanah Datar Regency is classified into three classes: low with an area of 10,391.27 ha (7.56%), medium with an area of 121,544.86 ha (88.44%), and high with an area of 5478.85 ha (4%). Comparison of soil air potential and ground air utilization in Tanah Datar Regency yielded nine classifications, namely low-low covering 2690.13 ha (1.95%), low-medium covering 6177.67 ha (4.5%), low-high 1523.43 ha (1.11%), medium-low 70060.54 ha (51%), medium-sized 36420.12 ha (25.5%), medium-high 15064.16 ha (10.96%), high-low 2957.85 ha (2.15%), high-medium 1244.21 ha (0.9%), and high 1276.87 ha (0.93%).